EVIDENCE OF SUBDUCTION AND CRUST-MANTLE MIXING FROM A SINGLE DIAMOND - Schulze D.J.; Harte B.; Valley J.W.; Channer D.M.DeR. (My University, 2004)
Cathodoluminescence (CL) imaging of polished sections of a diamond from the Guaniamo region of Venezuela suggests a history of the diamond involving two periods of growth separated by a period of resorption and possibly brittle deformation. In situ electron probe analysis of multiple eclogitic garnet inclusions reveals a correlation between garnet composition and location in the stone. An early-formed garnet in the diamond core has higher Ca/(Ca+Mg) and lower Mg/(Mg+Fe) values than later garnets associated with the second period of diamond growth. This variation conforms to an extensive trend of variation in the suite of eclogitic garnets extracted from Venezuelan diamonds. The diamond is zoned in carbon isotope composition (in situ secondary ion mass spectrometry, SIMS, data). The core compositions (δ13C PDB), corresponding to the first stage of growth, average −17.7‰. The second period of growth is apparently in two sub-sets of CL zones with mean values of −13.0‰ and −7.9‰. Nitrogen contents of diamond are low (30–300 atomic ppm) and do not correlate with carbon isotope composition. Oxygen isotope ratios of the garnet inclusions are elevated substantially above those expected for “common mantle”; δ18O VSMOW of early garnet is approximately +10.5‰ and two late garnets average +8.8‰. The evolutionary trend of magnesium enrichment in garnet is unlikely to represent igneous fractionation. The stable isotope data are consistent with diamond formation in subducted meta-basic rocks that had interacted with sea water at low temperatures at or near the sea floor and contained a substantial biogenic carbon component. During or following subduction, diamonds continued to form in an evolving system that was progressively modified by interaction with mantle material.
Keywords: Diamond; Garnet; Carbon isotopes; Oxygen isotopes; Subduction